Founding Visions : the Ideas, Individuals, and Intersections that Created America. - Banning, Lance, 1942-2006 (The University Press of Kentucky, 2014)
Lance Banning was one of the most distinguished historians of his generation. His first book, The Jeffersonian Persuasion: Evolution of a Party Ideology, was a groundbreaking study of the ideas and principles that influenced political conflict in the early American Republic. His revisionist masterpiece, The Sacred Fire of Liberty: James Madison and the Founding of the Federal Republic, received the Merle Curti Award in Intellectual History from the Organization of American Historians and was a finalist for the Pulitzer Prize. Banning was assembling this collection of his best and most repres.